Law No. 1 Of The Year 2021 Amending certain Provisions of the Traffic Law Promulgated by Law No. 66 Of The Year 1973 = قانون رقم 1 لسنة 2021 بتعديل بعض أحكام قانون المرور الصادر بالقانون رقم 66 لسنة 1973 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic